Effect of Polishing on the Surface Microhardness of Nanohybrid Composite Resins Subjected to 35% Hydrogen Peroxide: An In vitro Study - Cayo-Rojas, César Félix,2 (2021)
The use of bleaching agents, despite being a conservative treatment, can cause a decrease in the surface microhardness of dental resins, affecting their aesthetics and performance. The aim of this study was to evaluate the in vitro effect of polishing on the surface microhardness of nanohybrid composite resins that were subjected to bleaching with 35% hydrogen peroxide. Materials and Methods: This cross-sectional, in vitro experimental study consisted of 30 composite resin samples made according to ISO 4049-2019 and divided equally into two groups (A and B) which were subjected to 35% hydrogen peroxide bleaching. Group A was subjected to polishing procedure, whereas group B was the control group. The samples were stored in distilled water at 37°C for 24 h. The Vickers microhardness was determined with a load of 100 g-f for 10 s. The data were analyzed with Student’s t-test for independent samples at a confidence level of 95%. Results: The surface microhardness of the group that was subjected to polishing (A) obtained a mean of 78.07 ± 7.96 HV, whereas for the group that was not subjected to polishing (B) the mean was 65.67 ± 5.22 HV. The difference between groups (A and B) was statistically significant (P < 0.001). Conclusion: Nanohybrid composite resins previously subjected to 35% hydrogen peroxide gel significantly increased their surface microhardness when subjected to polishing when compared with unpolished nanohybrid composite resins